Interference patterns in ionization of Kramers–Henneberger atom - I. A. Ivanov; A. S. Kheifets; Kyung Taec Kim (Scientific Reports, 2022)
Abstract We combine IR pump and XUV probe laser pulses to visualize the Kramers–Henneberger (KH) state of the potassium atom. We demonstrate that ionization of such an atom exhibits some molecular-like features such as low order interference maxima in photoelectron momentum spectra. The locations of these maxima allow to estimate spatial dimensions of the KH atom and can be used for accurate calibration of high intensity laser fields. At the same time, we show that an analogy between the KH atom and a homo-nuclear diatomic molecule cannot be extended too far. In particular, higher order interference maxima are very difficult to observe in the case of the KH state. We attribute this to a particular structure of the KH potential which does not confine electron motion to a well-defined potential well unlike in real diatomic molecules.